Equivalent Single Layer Approach for Buckling Analysis of Stiffened Panel Under Bi-Axial Compression and Lateral Pressure - Teguh Putranto; Ardi Nugroho Yulianto; Dedi Budi Purwanto; Dony Setyawan (Institut Teknologi Sepuluh Nopember, 2023)
Ship structure composed of stiffened plates is subjected to a variety of loading conditions during service, which can lead to buckling. As a result of panel buckling, the overall strength of the ship hull girder is reduced, which is what determines the ultimate strength of the hull girder. The ultimate strength analysis can be accomplished with finite element (FE) simulation, but detailed modeling can be time-consuming. Due to these reasons, it is more advantageous and costeffective to replace the three-dimensional (3D) stiffened panel model with a two-dimensional (2D) equivalent single layer (ESL) plate. This shift from 3D to 2D is premised on the accuracy of ESL in representing the various buckling modes of stiffened panels, which are determined by panel topology and boundary conditions. Therefore, an equivalent single layer plate (ESL) that represents a stiffened panel is evaluated in different buckling modes. Considering that ESL is asymmetric in nature, any modification of the stiffened panel's geometry has a significant effect on the buckling modes. In this paper, we are concerned with two modes of buckling: (i) local buckling within the stiffeners of the plate and web, and (ii) local lateraltorsional buckling within the stiffeners. According to the results, ESL is capable of accurately predicting the effect of local buckling in combination of biaxial compression and lateral pressure.